From voluntary private to mandatory state governance in Indonesian forest certification: Reclaiming authority by bureaucracies - Agung Wibowo; Lukas Giessen (Forest and Society, 2018)
Forest certification has been introduced by non-state actors as a voluntary and market-based instrument addressing forest problems, which state policies failed to resolve. Lately, however, state-driven forest-related certification schemes can be observed, e.g. in Indonesia, through the EU FLEGT-VPA negotiation process. It is argued, specific state agencies in a struggle for power and authority develop mandatory certification schemes which are directly competing with private ones. Before this background, the aims of this study are: (i) describing the current trend from voluntary private to mandatory state certification schemes in Indonesia, (ii) mapping the main actors involved in certification politics, and (iii) explaining this trend with the interests of the main actors. The results confirm a trend from voluntary private to mandatory state-driven certification of forest management. The Ministry of Forestry, the Ministry of Trade, the Ministry of Industry, wood producer and processing associations, European Union, local funding organizations, environmental organizations, certification bodies and international buyers are detected as the main coalitions and actors in the certification politics. The stronger coalition develops a mandatorily-timber legality verification system as strategies to counter their voluntary private competitor schemes.